The mediating role of organizational citizenship behavior in the relationship between organizational transparency and school effectiveness - Tosun, Ali; Gidis, Yusuf (Kasetsart Journal of Social Sciences, 2026)
This study examines the effect of organizational transparency on school effectiveness and the mediating role of organizational citizenship behavior in this relationship. The study, designed as a correlational survey model, utilized Structural Equation Modeling (SEM) to analyze the data. The research sample consists of 327 teachers working in public schools. The findings reveal that teachers’ perceptions of organizational transparency significantly impact organizational citizenship behavior and school effectiveness. The results indicate that in schools with high levels of organizational transparency, teachers’ voluntary organizational citizenship behaviors increase, positively influencing the school’s effectiveness. Correlation analyses confirm significant positive relationships between organizational transparency, organizational citizenship behavior, and school effectiveness. Structural Equation Modeling further shows that organizational citizenship behavior partially mediates the relationship between organizational transparency and school effectiveness. In other words, organizational transparency enhances school effectiveness directly and through organizational citizenship behaviors. As a result, adopting a transparent management approach in schools is crucial for establishing effective schools.